Sudden impact - Choyce, Lesley, 1951- (2005)
When Kurt is hurt in a soccer game and ends up in the hospital Tina tries to help him, but nobody will tell her what is wrong, and Kurt's parents don't want her around. Tina learns that Kurt needs a donor with a rare blood type, and she finds a match in Kurt's soccer rival Jason. Jason agrees to donate his blood to Kurt, but when Kurt disappears from the hospital, the situation becomes desparate. Then Kurt's rival is in a tragic accident that may change everything.
Grade Level: 5-8.
HL570L Lexile.
Keywords: Donation of organs, tissues, etc. -- Juvenile fiction; Fiction; Juvenile works; Novels